2012
DOI: 10.3354/dao02443
|View full text |Cite
|
Sign up to set email alerts
|

Environmental persistence of amphibian and reptilian ranaviruses

Abstract: Ranaviruses infect fish, amphibians, and reptiles. The present study was conducted to compare the persistence of amphibian and reptilian ranaviruses in a pond habitat. The 4 viruses used in this study included 2 amphibian ranaviruses, Frog virus 3 (FV3, the type species of the genus Ranavirus) and an isolate from a frog, and 2 ranaviruses of reptilian origin (from a tortoise and from a gecko). A sandwich germ-carrier technique was used to study the persistence of these viruses in sterile and unsterile pond wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 25 publications
0
61
0
Order By: Relevance
“…Both Ranomafana and Andasibe are frequently visited by tourists and researchers and the movement of potentially contaminated footwear and equipment provides a likely vector for the spread of disease among and between biodiversity hotspots. Ranavirus can remain viable from days to weeks when protected from high temperatures, desiccation, and microbial action [54,55] providing considerable time for spread via fomites, and the same applies to Bd [56]. Even if these pathogens may be endemic to Madagascar, human-assisted introduction to naive isolated amphibian populations or the spread of different strains to new regions may lead to more severe outcomes and increased risk of declines.…”
Section: Discussionmentioning
confidence: 99%
“…Both Ranomafana and Andasibe are frequently visited by tourists and researchers and the movement of potentially contaminated footwear and equipment provides a likely vector for the spread of disease among and between biodiversity hotspots. Ranavirus can remain viable from days to weeks when protected from high temperatures, desiccation, and microbial action [54,55] providing considerable time for spread via fomites, and the same applies to Bd [56]. Even if these pathogens may be endemic to Madagascar, human-assisted introduction to naive isolated amphibian populations or the spread of different strains to new regions may lead to more severe outcomes and increased risk of declines.…”
Section: Discussionmentioning
confidence: 99%
“…Possible vectors have been investigated for both diseases, including contaminated water and amphibian trade (Brunner et al 2004, Johnson & Speare 2005, Harp & Petranka 2006, Greer et al 2008, Picco & Collins 2008, Nazir et al 2012, and although transmission of the chytrid fungus and the ranavirus can be influenced by anthropogenic disruptions (St-Amour et al 2008), such as habitat destruction and fragmentation (Phillips 1990), their presence in seemingly undisturbed areas led to alternate hypotheses about their transmission routes. For instance, migrating birds or other animals can act as vectors (Johnson & Speare 2005, Garmyn et al 2012, and climate change has been shown to alter host and pathogen distributions (Parra-Olea et al 2005, Pounds et al 2006) as well as susceptibility and virulence (Rojas et al 2005, Altizer et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…An important caveat is that all of these studies used virus grown in cell culture; ranaviruses shed in mucous, sloughed skin, etc., may be protected from microbes and the environment. Nazir et al ( 2012 ) also tested the persistence of ranaviruses in soil and found T-90s of 30-48 days, which raises concern over the potential for ranaviruses to be translocated in contaminated soil (Harp and Petranka 2006 ). Brunner et al ( 2007 ), however, found that ATV becomes noninfectious in pond substrate that is allowed to dry.…”
Section: Persistence Of Ranaviruses In the Environment And Carriersmentioning
confidence: 99%
“…In one study, LMBV lost 90 % of its infectivity in water in 24 h (its T-90 value), although it remained detectable in water for at least 7 days (Grizzle and Brunner 2003 ). Nazir et al ( 2012 ) found that four FV3-like viruses isolated from frogs, a tortoise, and a gecko had T-90s of between 22 and 34 days in unsterile pond water at 20 °C and up to 72 days at 4 °C, which is long enough to allow for continued transmission from the environment within an epidemic, if not between years. However, their experiment isolated virus particles from the direct action of microbes, which is problematic because bacteria and other microbes might otherwise be able to consume and inactivate pathogens.…”
Section: Persistence Of Ranaviruses In the Environment And Carriersmentioning
confidence: 99%